Penguatan Nilai Kejujuran Melalui Pendidikan Anti Korupsi di SD Negeri Kotakulon 1 Bondowoso - Adistia Nurwahyuni; Harizatun Najibah; Indri Maulani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to describe the application of anti-corruption education in strengthening honesty values among primary school students. The research used a qualitative descriptive approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The research informants consisted of two participants, namely the principal and one classroom teacher who were directly involved in implementing anti-corruption education at SDN Kotakulon 1 Bondowoso. The results showed that strengthening honesty values was carried out through habituation and role modeling, such as transparent management of class funds, habituation of academic honesty, and open activity reporting. Teachers served as key role models in the internalization of anti-corruption values, while family environmental factors became one of the obstacles affecting consistency of student behavior. The findings imply the importance of integrating habituation-based anti-corruption education in the learning process at primary schools, particularly within the context of Pancasila and Citizenship Education.